ADULT LONGEVITY OF Idea blanchardii (LEPIDOPTERA: NYMPHALIDAE) CAPTIVE BRED AT LIPI BUTTERFLY BREEDING FACILITY, CIBINONG, INDONESIA - Djunijanti Peggie; Supadi (Treubia, 2024)
Idea blanchardii is one of many endemic butterfly species in Sulawesi, Indonesia. This species is among the highly traded butterfly species thus requires biological information on the captive breeding. The aim of this study was to obtain data on the adult life-span, to report the multivoltine generation, and to provide conservation-related insight. Captive breeding research on this species was conducted within the period of September 2018 until February 2020. The host plant, Parsonsia alboflavescens, was used to support the life of this species for ovipositing and larval food plant. The adults would visit almost any flowers available at the facility. In total, 696 individuals were observed. Data on mating information of the species is presented here. Observations on when a female lays eggs are also revealed. This research showed that I. blanchardii is polygamous and polyandrous. Individuals of this species could live much longer than other butterfly species. A few could live over 80 days and one still seen laying eggs at the age of 136 days old.